PERANAN GULMA DALAM PENGELOLAAN LINGKUNGAN - Komang S. Padma Dewi W. (Bumi Lestari Journal of Environment)
Life creates and maintains environmental conditions as such, that is necessary tosupport life itself. Weeds, as part of living beings, are not plants out place, or out of time, butrather plants which their meanings, roles, and importances, for man in particular and life ingeneral are still unknown. The existence of weeds is not only for their spatial and trophicniches, but also for their multidimentional (in balancing environmental quality) and geneticniches. Therefore, weed control must be part of efforts in vegetation management. Variousefforts in weed management, in particular those with herbicides, from their production,distribution, storage, and applications must be based on their environmental feasibility, andnot just their economic and technological feasibilities.The development of weed management technology must be supported by scientificand technological studies, but the results must be translated in a simple and practical way forthe users and the farmers, since only simple innovations easy to understand and easy toimplement that will motivate efforts for a better cultural practices.